(untitled) (Bangladesh Journal of Plant Taxonomy, 2017)
A new species of the genus Synechococcus C. Nägeli was described from extreme environment (high salinity) of the Yuncheng salt lake, North China. Morphological characteristics observed by light microscopy (LM) and transmission electron microscopy (TEM) were described. DNA barcodes (16S rRNA+ITS-1, cpcBA-IGS) were used to evaluate its taxonomic status. This species was identified as Synechococcus salsus H. Lv et S. Xie. It is characterized by unicellular, without common mucilage, cells with several dispersed or solitary polyhedral bodies, widely coccoid, sometimes curved or sigmoid, rounded at the ends, thylakoids localized along cells walls. Molecular analyses further support its systematic position as an independent branch. The new species Synechococcus salsus is closely allied to S. elongatus, C. Nägeli, but differs from it by having shorter cell with length 1.0–1.5 times of width. Bangladesh J. Plant Taxon. 24(2): 137–147.